The Effect of a Designed Respiratory Care Program on the Incidence of Ventilator-Associated Pneumonia: A Clinical Trial - Mohammad Abbasinia; Nasim Bahrami; Soheila Bakhtiari; Ahmadreza Yazdannik; Atye Babaii (Journal of Caring Sciences, 2016)
Introduction: Ventilator-associated pneumonia is a common complication of mechanical ventilation. This study aimed to evaluate the effect of designed respiratory care program on incidence of ventilator-associated pneumonia (VAP) in the mechanically ventilated patient. Methods: In this clinical trial, 64 patients were selected among those who had undergone mechanical ventilation in the ICU of Al‑Zahra Hospital, Isfahan, Iran, using convenience sampling method. The subjects were randomly allocated to intervention and control groups. In the intervention group an upper respiratory care program and in the control group, routine cares were done. Modified Clinical Pulmonary Infection Questionnaire was completed before and on the third, fourth and fifth day of study. Data were analyzed by Chi-square and independent t-test through SPSS Ver.13. Results: The results of this study showed that until the third day of study, the incidence of VAP was similar in the both groups. However, on the fifth day of study, the incidence of VAP in the intervention group was significantly lower than control group. Conclusion: The results of this study showed that an upper respiratory care program reduced the incidence of VAP. Therefore, nurses are recommended to perform this program for prevention of VAP.